Saving erythropoietin by administering l-carnitine? - Bommer, Jürgen (Nephrology, dialysis, transplantation, 1999)
Recombinant human erythropoietin (rhEpo) is widely used for correction of anaemia in patients with end-stage renal disease (ESRD). In some countries, the cost o
Gesehen am 12.10.2020